Covariant differential calculus on SPh2|1 - Celik, Salih; Temli, Ilknur (Tubitak Scientific & Technological Research Council Turkey, 2019)
The h-deformed symplectic superspaces via a contraction of the q-deformed symplectic superspaces are introduced and a covariant differential calculus on the quantum symplectic superspace SPh2 vertical bar 1 is presented.
Keywords: Quantum symplectic superspace; quantum supergroup; super-Hopf algebra; quantum differential calculus; QUANTUM DEFORMATION; Mathematics